Espectrometria de absorção atômica como ferramenta analítica para determinação de elementos traço em biodiesel - Lyra, Fernanda Henrique (2010)
In this work some procedures were developed for the determination of Na, K, Ca, Mg and P in biodiesel samples using atomic absorption spectrometry as an analytical tool. The determination of Na, K, Ca and Mg in biodiesel samples was performed using the technique of flame atomic absorption spectrometry (F AAS) and microemulsion as sample preparation. The optimum composition of the microemulsion was 10% biodiesel, 75% n-propanol, 1% concentrated nitric acid and 14% aqueous solution. The stability study showed that the analytical signals in the biodiesel as microemulsion remained stable for a period of 15 days. The analytical curves were obtained using organometallic standard solutions. The values of the limits of detection (LOD) of 0.1 µg g-1, 0.01 µg g-1, 0.03 µg g-1, and 0.003 µg g-1 were found for Na, K, Ca and Mg respectively. The accuracy of the proposed procedure was verified by comparison with an independent procedure (ABNT 15556) and by recovery tests. The results indicated a good accuracy of the proposed procedure considering the t-Student test (p <0.05) and the recovery values obtained (94-103%). The determination of P in biodiesel samples was performed using the technique of atomic absorption spectrometry graphite furnace with a solid sampling accessory (SS-GF AAS). No pretreatment of the sample was necessary. A better analytical signal was obtained when the solution of the Pd modifier in Triton X-100 was dispensed on the samples. The pyrolysis (1300 ºC) and atomization (2700 ºC) temperatures and the mass of Pd (30 mg) were defined by multivariate optimization. The other parameters of the temperature program were defined by univariate optimization. The analytical curves were obtained using aqueous standards (R2 = 0.9939). The limit of detection in the optimized conditions was 7.2 ng (1.4 µg g-1) and the characteristic mass was of 9.1 ng. The evaluation of the accuracy of the proposed method was performed by analysis of reference materials, as well as by comparison with an independent procedure (EN 14107). No statistical difference was observed considering the t-Student test (p <0.05)